2016
DOI: 10.4103/2231-0762.192935
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis to the oral soft tissues: A review of 412 cases

Abstract: The present review article analyzes the characteristics of metastases to the oral soft tissues from 1937 to 2015. An extensive literature search was performed. All variables such as age, gender, and primary and secondary tumor sites were analyzed. Metastases to the major salivary glands were not included in this review. In general, there were 412 metastatic lesions developed in the oral soft tissues. The male-to-female ratio was approximately 1.8:1. The mean age of the patients at diagnosis was 58. The lung wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 216 publications
0
59
1
2
Order By: Relevance
“…[2] Metastasis to the jaw bones mainly occurs in the posterior region of the mandible, ramus, and the condyle, which are rich in red bone marrow. Metastasis to the maxilla is rare and comprises one-fifth of all metastatic tumors to the jawbones.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Metastasis to the jaw bones mainly occurs in the posterior region of the mandible, ramus, and the condyle, which are rich in red bone marrow. Metastasis to the maxilla is rare and comprises one-fifth of all metastatic tumors to the jawbones.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous literature review referring to 412 cases [5], Irani found that only 33% of oral metastases affected the soft tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation of gingiva may provide adequate conditions for metastatic tumour cell colonisation [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%
“…Malignant tumours of the lung, breast, kidney, liver, bone, prostate, thyroid gland, skin, colon and female genital organs most commonly give metastases in oral region. The incidence of metastatic tumours of oral region is rising, according to the fact that patients with cancers live longer due to advances in cancer diagnosis and management 2,[4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation